2010
DOI: 10.1177/0022343310371881
|View full text |Cite
|
Sign up to set email alerts
|

From toys to warships: Interdependence and the effects of disaggregated trade on militarized disputes

Abstract: The United States recently proposed to sell Saudi Arabia advanced weaponry worth 20 billion dollars over the next 10 years. The volume of trade, while significant, is second in the news headline that the United States would provide Saudi Arabia with precision-guided bombs, upgrades to its fighters, and new naval vessels. Trade of strategic commodities, such as armaments, suggests a strong interdependence between countries, which may influence international relations differently than the same volume of toys tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…A limitation is that I do not directly explore the role of firms or other sub-state actors, or of different types of traded goods in each stage of the conflict process. Some research has shown that not all traded goods are equal in their potential role in conflict (Dorussen 2006;Dorussen and Ward 2011;Goenner 2010), which is consistent with my approach and a promising area for further inquiry.…”
Section: Theoretical Discussion and Hypothesessupporting
confidence: 83%
“…A limitation is that I do not directly explore the role of firms or other sub-state actors, or of different types of traded goods in each stage of the conflict process. Some research has shown that not all traded goods are equal in their potential role in conflict (Dorussen 2006;Dorussen and Ward 2011;Goenner 2010), which is consistent with my approach and a promising area for further inquiry.…”
Section: Theoretical Discussion and Hypothesessupporting
confidence: 83%
“…With a few exceptions (Goenner, 2010) The results indicate that countries with oil rents acknowledge the instability of the oligopolistic market that oil belongs to, and they choose a pacifier's behavior in their relations with other states. Countries with rents from monopolistic and free markets products -although very different structures-behave similarly with a positive relationship to crisis initiation.…”
Section: Resultsmentioning
confidence: 87%
“…They are therefore important for the well-being of all voters, not only a limited group. Some limited application of the qualitative research tradition into the quantitative research has been applied by Dorussen (2006) and Goenner (2010). In analysing the trade in strategic commodities, both sensitivity and vulnerability come into play -sensitivity traditionally reflecting the amount of trade and vulnerability reflecting the cost of being hurt by the discontinuation of the trade (Barbieri 2003).…”
Section: Theories and Hypotheses Commercial Liberalismmentioning
confidence: 99%
“…In order to look only at the strategic goods, I employ the categorization and list developed by Goenner (Goenner 2010). In one of the sub-models, I focus particularly on the trade in energy (oil, natural gas, coal, and electricity).…”
Section: Independent Variablesmentioning
confidence: 99%